2010
DOI: 10.1186/1471-2407-10-471
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment alters epigenetic and gene expression profiles in Swarm rat chondrosarcoma tumors

Abstract: BackgroundChondrosarcomas are malignant cartilage tumors that do not respond to traditional chemotherapy or radiation. The 5-year survival rate of histologic grade III chondrosarcoma is less than 30%. An animal model of chondrosarcoma has been established - namely, the Swarm Rat Chondrosarcoma (SRC) - and shown to resemble the human disease. Previous studies with this model revealed that tumor microenvironment could significantly influence chondrosarcoma malignancy.MethodsTo examine the effect of the microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 61 publications
0
54
0
Order By: Relevance
“…Results showed that the SRC tumor tissues exhibited a lower methylation level than normal cartilage. Specifically, statistically significant differences of methylation levels were revealed among SRC tumors tissues in different transplantation sites [20]. These findings indicated that DNA methylation may be regulated by microenvironment changes, providing insight into the influence of environmental factors on DNA methylation alterations in CS.…”
Section: Dna Hypomethylation In Csmentioning
confidence: 78%
See 4 more Smart Citations
“…Results showed that the SRC tumor tissues exhibited a lower methylation level than normal cartilage. Specifically, statistically significant differences of methylation levels were revealed among SRC tumors tissues in different transplantation sites [20]. These findings indicated that DNA methylation may be regulated by microenvironment changes, providing insight into the influence of environmental factors on DNA methylation alterations in CS.…”
Section: Dna Hypomethylation In Csmentioning
confidence: 78%
“…It can occur at normally methylated DNA sequences as repetitive DNA sequences and gene regulatory regions, and can be classified into two subtypes: global hypomethylation (loss of total DNA methylation content) and individual gene hypomethylation (e.g., hypomethylation of an oncogene) [17]. Since repetitive DNA sequences, such as satellite 2 and LINE-1, make up approximately 50% of the genome, their hypomethylation always acts as a marker for evaluating global hypomethylation that is a frequent event in human malignancies, including Swarm rat CS (SRC), which has been shown to resemble the human disease [17][18][19][20]. In a 2009 study, global hypomethylation was induced by using decitabine in SRC, a rat model of human CS [18,[20][21][22][23].…”
Section: Dna Hypomethylation In Csmentioning
confidence: 99%
See 3 more Smart Citations